SUBSTANTIVE CHARACTERISTICS OF PROFESSIONAL IMAGE: BEFORE STATING THE PROBLEM - L.I. Kuchyna (Academy of Cognitive and Natural Sciences, 2022)
It is main to collect the professional prepearing of future tcachers imidgining as a part of methodological culture